Pengenalan IoT Dalam Pengembangan Energi Terbarukan Dengan TNI (Kodim 0820) di Universitas Panca Marga - Hartawan Abdillah; Mas, Ahmad Baihaqi; Dani Hari Tunggal Prasetiyo; Alief Muhammad; Tamam Asrori; Linda Kurnia; Citra Suardi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The development of renewable energy is becoming increasingly important in addressing the challenges of climate change and the growing energy demand. One promising approach is the utilization of the Internet of Things (IoT), which enables efficient and coordinated energy management. In this context, community service activities were conducted in collaboration with the TNI Kodim 0820 to socialize the use of IoT in the development of renewable energy. Through lectures, training sessions, and demonstrations of installing solar power systems (PLTS) and wind power systems (PLTB), participants were introduced to the concepts and benefits of IoT in renewable energy. The aim of these activities is to enhance the knowledge, skills, and participation of the community in managing renewable energy. The results of the activities show that the collaboration between Panca Marga University and TNI Kodim 0820 contributes positively to accelerating the transition towards cleaner, more efficient, and sustainable energy. These initiatives are expected to serve as a foundation for larger and more sustainable renewable energy development projects in the future.